Advent of Diversity Management and Inclusion in Nepalese Organizations The Role of Government and International Agencies - Sundas, Ujjwal (A Bi-annual South Asian Journal of Research & Innovation, 2024)
Nepal has been practicing theories of Human Resources Management (HRM) in the organizations only from few decades. The Diversity and Inclusion (D&I) are the relatively new topics in the country. In the 1980s, diversity management (DM) concepts first appeared in the United States. The majority of the European Union’s industrialized nations have led the way in diversity management. No research hasn’t been done on how HRM has changed as a field or how inclusion and diversity are now considered and discussed in Nepalese organizations. Examining the state of DM and included in Nepalese organizations will aid in shaping HR professionals’ and legislators’ perspectives on the importance of DM and I in Nepal. This study is basically based on desk review with the qualitative approach. Larger corporations in Nepal are still struggling to understand workplace inclusion and equality, though the community and nonprofit organisations have demonstrated a greater level of interest. In order to spread awareness of diversity and inclusion in the nation, several industries have taken some action. The article was developed by carefully reviewing previous, pertinent papers and articles. The article attempts to provide an exploratory review seeking to perspectives of Nepal government and international agencies regarding D&I through rigorous analysis of the available literature. This article discusses the government policies and initiatives take by international agencies to foster D& I in Nepal. The UN related organizations and ILO in Nepal have been emphasizing continuously for the need of adopting the principles of D&I in the human of profit making and non-profit making organizations in the country. The preamble of Nepalese Constitution 2015 has highlighted the inclusion to be ensured in all the structures of the government and the private sectors. The UN agencies and ILO Nepal in Nepal have taken remarkable steps for promoting the principles of D&I through Gender Equality and Social Inclusion (GESI) and other frameworks in the non-profit and profitmaking organizations in Nepal.